Characterization of (GT)n and (CT)n microsatellites in two insect species: Apis mellifera and Bombus terrestris. - Estoup, A (1993)
A set of 52 (CT)n and 23 (GT)n microsatellites in honeybee, 24 (CT)n and 2 (GT)n microsatellites in bumble-bee (n > 6) have been isolated from partial genomic libraries and sequenced. On average, (CT)n and (GT)n microsatellites occur every 15 kb and 34 kb in honeybee and every 40 kb and 500 kb in bumble-bee, respectively. The prevailing categories are imperfect repeats for (CT)n microsatellites in bumble-bee, and perfect repeats for both (CT)n and (GT)n microsatellites in honey-bee. Comparisons with data available in vertebrates indicate a lower proportion of perfect repeats in bees but length distributions are very similar regardless the phylum. This result extends to insects the concept of an evolutionary conservation for quantitative and qualitative characteristics of (CT)n and (GT)n microsatellites. Many (CT)n and (GT)n repeats are surrounded with various types of microsatellites, revealing an associative distribution of short repeat sequences. As expected, a high level of intrapopulational polymorphism has been found with one tested honeybee microsatellite. Also, flanking regions of this microsatellite are similar enough to allow PCR amplification in several other species of Apis and Bombus.